Unraveling most abundant mutational signatures in head and neck cancer - Plath, Michaela; Gass, Johanna; Hlevnjak, Mario; Li, Qiaoli; Feng, Bohai; Hostench, Xavier Pastor; Bieg, Matthias; Schroeder, Lea; Holzinger, Dana; Zapatka, Marc; Freier, Kolja; Weichert, Wilko; et al. (International journal of cancer, 2021)
What's new? Progression of head and neck squamous cell carcinoma (HNSCC) is associated with the accumulation of multiple genetic and epigenetic alterations. Elucidating these mutational processes and...
First published: 15 September 2020
Gesehen am 13.12.2021